A critical review on energy recovery and non-hazardous disposal of oily sludge from petroleum industry by pyrolysis - Li, Jiantao; Lin, Fawei; Li, Kai; Zheng, Fa; Yan, Beibei; Che, Lei; Tian, Wangyang; Chen, Guanyi; Yoshikawa, Kunio (Journal of hazardous materials, 2021)
This review systematically reports the pyrolysis of oily sludge (OS) from petroleum industry in regards to its dual features of the energy recovery potential and the environmental risks. The petroleum hydrocarbons are the nonbiodegradable fractions in OS that possess hazardous properties, i.e. ignitability and toxicity. Besides, complicated hazardous elements (i.e. N, S and Cl) and heavy metals inherently existing in OS further aggravate the environmental risks. However, the high oil content and heating value of OS contribute to its huge energy resource potential. Considering the energy demand and the environmental pressure, the ultimate purposes of the OS management are to enhance the oil recovery efficiency to minimize the oil content as well as to stabilize the hazardous elements and heavy metals into the solid residue. Among various OS management technologies, pyrolysis is the most suitable approach to reach both targets. In this review paper, the pyrolysis principle, the kinetics and the product distribution in three-phases are discussed firstly. Then the effects of operating parameters of the pyrolysis process on the quality and the application potential of the three-phase products, as well as the hazardous element distribution are discussed. To further solve the dominant concerns, such as the oil content in the solid residue, the pyrolytic oil quality and the migration of hazardous elements and heavy metals, the potentials of the catalytic pyrolysis and the co-pyrolysis with additives are also summarized. Also, the typical pyrolysis reactors are then presented. From the perspective of the energy efficiency and the non-hazardous disposal, the integrated technology combining the pyrolysis and the combustion for the OS management is recommended. Finally, the remaining challenges of OS pyrolysis encountered in the research and the industrial application are discussed and the related outlooks are itemized. [Display omitted] •Energy recovery and non-hazardous disposal are dual targets for OS pyrolysis.•The OS characteristics with energy potential and environmental risk are summarized.•This review focuses on valuable products distribution and harmful components flow.•The advantages and future challenges for OS pyrolysis are proposed and outlooked.